Framework for Gamification of Online Training Platforms for Employee Engagement Enhancement - Alfaqiri, Abdullatif Saleh; Noor, Siti Fadzilah Mat; Sahari, Noraidah (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Organizations have moved away from traditional classroom-based training to online training whereby employees can attend courses at their convenience either at home or in the workplace. This transition has been fuelled by lockdowns that governments worldwide have implemented to counter the spread of the COVID-19 pandemic, where employees are expected to work or attend training from home. However, several issues including lack of employee engagement hinder the effective delivery of online corporate training. In recent years, gamification has been identified as a solution to lack of engagement in education. Gamification involves the incorporation of game elements into non-game applications to encourage user engagement, where different combinations are used for different learning contexts. However, little research has been done to identify suitable game elements for the gamification of corporate online training. This study proposes a set of game elements to improve employee engagement with online training platforms. A step-by-step analysis of the literature led to the identification of nine potentially suitable game elements. These elements were evaluated by a group of experts selected from five well-known training providers in Saudi Arabia, who completed a semi-structured interview questionnaire about the usability, completeness, and usefulness of the elements. The result of the evaluation indicated that the identified game elements will be able to effectively and efficiently improve employee engagement. The set of nine game elements was then incorporated into a proposed framework for the gamification of online training platforms to enhance employee engagement.